Factores actitudinales académicos en estudiantes de pre grado frente a la elaboración de la tesis en la Universidad Nacional de Trujillo sede Huamachuco 2017 - II - Paredes Gaitan, Yossed Alexander (2018)
The present investigation was carried out with the purpose of determining if the attitudinal academic factors have multidimensional nature and which of them are the most representative that the students hold at the moment of elaborating their thesis in the national university of Trujillo, Huamachuco campus, 2017; being a descriptive investigation, for which a survey instrument was applied whose interpretation was given under the Likert scale. The statistical program SPSS 24 and Excel 2014 were mainly used to verify a multidimensional nature of attitudes; With the analysis of main components in a sample population of 114 students; Finding that it is structured by 3 factors that explain 46,861% of the total inertia